Development of a Teleoperation System for Controlling a Scaled Prototype Robot for Rescue Tasks in Natural Disasters - Aguilar, Ivan; Barrios, Dennis (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
This study addresses the critical problem of teleoperation for search and rescue (SAR) robots, focusing on the development of a robust teleoperation system utilizing a customized communication infrastructure based on Long Range (LoRa) Low Power Wide Area Network (LPWAN). This system ensures long-range communication and low energy consumption between the robot and the base station, facilitating effective and safe control of the robot’s actions with minimal latency. The implementation of a two-LoRa configuration stands out to improve teleoperation capabilities, such as bidirectional parallel communication and more reliable communication by focusing each module on a specific function. The solution includes the creation of an intuitive and robust graphical user interface, incorporating Human-Robot Interaction (HRI) principles to enhance usability. This interface allows operators to view data captured by the robot’s sensors and monitor battery status. Additionally, this study emphasizes the construction of a low-cost prototype using 3D printing technologies, aiming to validate and optimize the design through experiments and tests in SAR scenarios. During these tests, the robot was successfully monitored and controlled from a remote base station to know the maneuverability it offers. Additionally, tests were performed to determine the maximum coverage range, taking into account the attenuation caused by surrounding buildings in an urban space.